Pengaruh Likuiditas, Profitabilitas, dan Solvabilitas terhadap Kinerja Keuangan Bank Syariah yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023 - Numberi, Camelia Lusandri; Tamher, Khoiriati; Werimon, Simson; Malino, Marlina (Lensa Ekonomi, 2025)
This study aims to analyze the effect of liquidity, profitability, and solvency on the financial performance of Islamic banks listed on the Indonesia Stock Exchange in 2020-2023. This research uses a quantitative approach with multiple linear regression analysis methods. The data used is secondary data from the annual financial statements of four Islamic banks selected through purposive sampling technique, namely PT Bank Aladin Syariah Tbk, PT Bank Syariah Indonesia Tbk, PT Bank BTPN Syariah Tbk, and PT Bank Panin Dubai Syariah Tbk. The independent variables in this study are liquidity (Current Ratio), profitability (Return on Assets), and solvency (Debt to Asset Ratio), while the dependent variable is financial performance (Return on Equity). The analysis results show that partially, only profitability has a significant effect on financial performance. Meanwhile, liquidity and solvency have no significant effect partially. But simultaneously, the three variables have a significant effect on the financial performance of Islamic banks.